Implementation and Realization of GNSS Signals Acquisition and Tracking Algorithm - Fuguo Xin; Rongfang Li (Dianxin kexue)
Based on the observation of frequency spectrum of navigation signal, an improved FFT acquisition algorithm was proposed which could reduce the capturing time of GNSS receiver, the threshold of the algorithm was also modified. Simulation results show that the new algorithm can shorter capturing time. The complete tracking channel of the GNSS receiver was also designed, and the MATLAB simulation results verify the correctness of the proposed tracking channel.